2011
DOI: 10.1039/c0cs00199f
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and application of polyamino polycarboxylic bifunctional chelating agents

Abstract: Bifunctional chelating agents (BFCAs) are molecules which contain two different moieties: a strong metal chelating unit and a reactive functional group. The latter is directed to react with amines, thiols, alcohols or other reactive molecules to form stable covalent bonds while the chelating moiety is able to strongly coordinate a metal ion. In this way, it is possible to label a molecule of interest (e.g. an antibody or a peptide) with a metal or a radioactive metal ion. Of all the ligands reported so far, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 304 publications
(393 reference statements)
1
118
0
1
Order By: Relevance
“…Overall, from our data we concluded that procainamide molecule is highly melanin specific, however, the properties of the used bifunctional chelator (BFC) determines the accumulation of the labeled compound in melanin postive melanoma cells and tumors. From an ideal BFC can expect the following properties: -fast complexation at a very low ion-concentration range, preferably at room temperature, -tolerance of a broad pH range, -and selectivity against the endogenous metal ions (Ca or Zn) or potential impurities originated from the production of the radionuclide (Fe or Al) [13,32]. The final radiolabeled compound should be resistant of the challenge of different endogenous ligands, such as transferrin or lactoferrin [33].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, from our data we concluded that procainamide molecule is highly melanin specific, however, the properties of the used bifunctional chelator (BFC) determines the accumulation of the labeled compound in melanin postive melanoma cells and tumors. From an ideal BFC can expect the following properties: -fast complexation at a very low ion-concentration range, preferably at room temperature, -tolerance of a broad pH range, -and selectivity against the endogenous metal ions (Ca or Zn) or potential impurities originated from the production of the radionuclide (Fe or Al) [13,32]. The final radiolabeled compound should be resistant of the challenge of different endogenous ligands, such as transferrin or lactoferrin [33].…”
Section: Discussionmentioning
confidence: 99%
“…15 Hence, this dithiocarbamate of isonipecotic acid can act as a bifunctional chelating agent 16 (BFCA) because it can work as a linker between the metal (bonded to the dithiocarbamate function) and the biomolecule (bonded by a peptidic bond).…”
Section: (Scheme 1)mentioning
confidence: 99%
“…Interestingly, after about 7 h post-injection the contrast enhancement observed for the more efficient liposomes decreases rapidly and becomes lower than for LIPO-GdDOTAMA(C 18 ) 2 . The relaxometric data and the quantification of the Gd III complexes in the organs, determined ex vivo by inductively coupled plasma mass spectrometry, indicate that: 1) the differences in the contrast enhancement can be attributed to the different rate of water exchange and rotational dynamics of the Gd complexes, and 2) the rapid contrast decrease is caused by a faster clearance of GdDOTA(GAC 12 ) 2 from the organs. This is also confirmed by using a newly synthesised amphiphilic cyanine-based fluorescent probe (Cy5-(C 16 ) 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The complexes differ in one donor group of the coordination cage (carboxylate versus carboxoamide), and in the length (C 12 versus C 18 ) and the point of attachment of the aliphatic chains to the chelators. The in vitro 1 H relaxometric characterisation of the systems, performed with a newly developed relaxation model that takes into account the contributions of the Gd III chelates pointing in-and outwards of the liposome, indicates that their efficacy is optimal in the range 0.5-1.5 T. The tetracarboxylic C 12 -containing liposomes (LIPO-GdDOTA(GAC 12 ) 2 ; GA = glutaric acid) are four-fold more efficient than the monoamide C 18 -based analogue (LIPO-GdDOTAMA(C 18 ) 2 ). Such a difference is also found in vivo at 1 T in a melanoma tumour model on mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation